18F-FDG PET/CT for Early Postradiotherapy Assessment in Solitary Bone Plasmacytomas. (August 2015) - Alongi, Pierpaolo; Zanoni, Lucia; Incerti, Elena; Fallanca, Federico; Mapelli, Paola; Papathanasiou, Nikolaos; Gianolli, Luigi; Picchio, Maria; Bomanji, Jamshed
Abstract : Purpose: The purpose of this study was to evaluate the performance and possible prognostic value of early 18 F-FDG PET/CT (FDG PET/CT) assessment after radiotherapy (RT) in patients with solitary bone plasmacytoma (SBP). Methods: Twenty-one patients affected by SBP who underwent FDG PET/CT scan for early restaging (⩽6 months) postradiotherapy assessment were selected from the PET databases of University College London Hospital of London and San Raffaele Hospital of Milan. Patients with no abnormal uptake were classified as having no pathologic uptake (NPU). A SUVmax cutoff value of 4 was chosen to discriminate minimal residual uptake (MRU; SUVmax ⩽ 4) from pathologic uptake (PU, SUVmax >4). Progression-free survival (PFS) rate was estimated using Kaplan-Meier curves and Cox regression analysis. Results: In 10 of 21 patients restaged by FDG PET/CT, further previous baseline scan was available also at staging, and results showed positive findings at the level of all biopsy-proven disease areas. Considering MRU as PU, FDG PET/CT showed a sensitivity and specificity of 86% and 29%, respectively. Using SUVmax >4 as the cutoff, sensitivity and specificity were 86% and 93%, respectively. Kaplan-Meier curves revealed a significant difference in PFS probability between patients classified as positive on FDG PET/CT using a cutoff of SUVmax >4 (PU) and those classified as negative (NPU + MRU) (log-rank, Mantel-Cox, P = 0.009; χ 2 = 6.85). Cox regression analysis of PFS using SUVmax >4 as cutoff revealed an interesting relation in prediction of progression (HR, 9.458). Conclusion: 18 F-FDG PET/CT for early restaging after RT in patients with SBP should be considered carefully in view of the lack of specificity of a low SUVmax value. The good correlation between a high SUVmax value and follow-up suggests a possible prognostic role for FDG PET/CT in disease progression at early restaging after RT.